Morphological and Pomological Diversity of Fig (Ficus carica L.) Cultivars in Northwest of Tunisia. (10th July 2012) - Gaaliche, Badii; Saddoud, Olfa; Mars, Messaoud
Abstract : The fig ( Ficus carica L.) is one of the oldest fruit trees cultivated in Tunisia. Djebba region is located in the northwest of Tunisia. It is very famous by fig culture. Many specific fig genotypes are very appreciated locally and nationally. Taking into account these considerations, Djebba fig cultivars are subject of label products, namely, "Djebba figs." This study was focused on fig germplasm characterization of 17 cultivars in Djebba region based on morphological and pomological traits. Results revealed a large variability within the local fig germplasms. The comprehensive analyses of all the data permitted to distinguish some particular genotypes as distinct cultivars, and groups of cultivars as polyclone varieties. It was possible to discriminate six distinct cultivars and two groups of multiclone varieties ( Soltani and Thgagli ) with different degrees of polymorphism. Hypotheses of homonymy and synonymy were suggested for some cultivars. The diversity is currently threatened by genetic erosion. Measure of conservation is necessary to be undertaken.